ETHANOL LEAF EXTRACT OF FICUS EXASPERATA ATTENUATES CHANGES IN ELECTROLYTES AND LIPID PROFILES IN A RAT MODEL OF OLANZAPINE-INDUCED OBESITY (FUDMA JOURNAL OF SCIENCES, 2025)
Obesity is a major public health concern characterized by excessive body fat, which increases the risk of numerous health conditions, including heart disease, diabetes, high blood pressure, and certain cancers. Addressing obesity is crucial for improving overall health and well-being. In this study, thirty female Wistar rats, weighing between 190 and 200 g, were utilized to investigate the effects of Ficus exasperata on olanzapine-induced obesity.  After a two-week acclimatization period, obesity was induced in the designated group using olanzapine (4 mg/kg) via oral gavage for 28 days. The rats were then divided into five groups (n = 6): normal control, obese-untreated, non-obese treated with Ficus exasperata (100 mg/kg), obese treated with Ficus exasperata (100 mg/kg), and obese treated with orlistat (100 mg/kg). Treatments were administered orally for 28 days. At the end of the study, the animals were sacrificed, and blood samples were collected for serum analysis. The study demonstrated that Ficus exasperata significantly (P< 0.05) increases bicarbonate and potassium while reducing sodium and calcium (P< 0.05). Ficus exasperata significantly (P< 0.05) reduces HDL with a significant (P< 0.05) increase in TC, TG and LDL. These findings suggest that Ficus exasperata influences both electrolyte balance and lipid metabolism in obese animals.
Keywords: Ficus exasperata; Electrolytes; Lipid profiles; Olanzapine-induced obesity; Ethanol leaf extract